2012
DOI: 10.1093/ilar.53.3-4.341
|View full text |Cite
|
Sign up to set email alerts
|

The Human Imprintome: Regulatory Mechanisms, Methods of Ascertainment, and Roles in Disease Susceptibility

Abstract: Imprinted genes form a special subset of the genome, exhibiting monoallelic expression in a parent-of-origin–dependent fashion. This monoallelic expression is controlled by parental-specific epigenetic marks, which are established in gametogenesis and early embryonic development and are persistent in all somatic cells throughout life. We define this specific set of cis-acting epigenetic regulatory elements as the imprintome, a distinct and specially tasked subset of the epigenome. Imprintome elements contain D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 161 publications
(199 reference statements)
3
70
0
1
Order By: Relevance
“…3C), in agreement with the data in haematopoietic malignancies [26]. Together, our data validate IRAIN as a new member of the family of imprinted genes [41].…”
Section: Discussionsupporting
confidence: 89%
“…3C), in agreement with the data in haematopoietic malignancies [26]. Together, our data validate IRAIN as a new member of the family of imprinted genes [41].…”
Section: Discussionsupporting
confidence: 89%
“…S20), which is consistent with imprinted genes often being growth regulators (Skaar et al 2012;Lawson et al 2013). Without dosage compensation, silencing of one allele via imprinting should halve expression levels (Susiarjo et al 2013).…”
Section: Expression and Methylation Of Imprinted Genessupporting
confidence: 62%
“…S6; Skaar et al 2012;Court et al 2014). Analysis of the methylation array data in the GenCord data set showed that imprinted genes had a Figure 2.…”
Section: Expression and Methylation Of Imprinted Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CTCFL gene is not directly associated with any genetic disorder, it is believed to participate in some epigenetic mechanisms. Since the CTCFL gene has been found to be associated with the regulation of several imprinting control regions [Skaar et al, 2012] and the patient has growth retardation and body asymmetry typical for many imprinting disorders, an analysis of imprinted regions in chromosomes 6, 7, and 14 was additionally performed.…”
Section: Genetic Testing and Resultsmentioning
confidence: 99%